Self-Disclosure and Adapt Communication in the New Workplace - Ashofa Purnamasari (Jurnal Ilmu Komunikasi, 2022)
The newcomers within an organization must carry out a socialization process, therefore, employee onboarding into organizations is seen as essential for the process of adaptation to the organizational culture. One of the things newcomers can do during the socialization process is to adapt and get to know the organization and the actors in the organization through adapt communication. This study seeks to find out how newcomers in MAX Academy and PT ARISTA organizations manage self-disclosure in the organization through the socialization process; early socialization, encounter, and metamorphosis.  The results have revealed that in the newcomer self-disclosure practice there are limitations in self-disclosure to colleagues, such as age gap and educational status. However, the lack of self-disclosure does not prevent newcomers from continuing to carry out the socialization process with various predetermined stages. Additionally, the observed companies have different styles in fostering new employees in the socialization process, namely MAX Academy provides a program called onboarding to help newcomers in the socialization process, meanwhile PT ARISTA gives fully authority to newcomers to use their own model in the socialization process into the new organizational culture